Hypersato Structures - Cuadros Valle, Jaime (2013)
We define hypersato structures: these structures admit three inequivalent Sasakian structures such that each of these structures shares a common Reeb vector field and a common contact form with the others two. It is interestingto notice that hypersato manifolds can be viewed as U(1) principal orbibundles with base space a 4n-dimensional hyperkahler orbifold. We also discuss some results on the moduli problem of these structures.